Tau phosphorylation in transgenic mice expressing glycogen synthase kinase-3beta transgenes. - Brownlees, J; Irving, N; Brion, J; Gibb, B; Wagner, U; Woodgett, J; Miller, C (1997)
In order to investigate the effect on tau of manipulating glycogen synthase kinase (GSK)-3beta activity in the brain, we created transgenic mice harbouring wild-type GSK-3beta genes or a mutant GSK-3beta that is predicted to be more active. Transgene-derived mRNAs were detected in the brains of a number of the transgenic mouse lines and several of these transgenic lines displayed transgenic GSK-3beta activity. Western blot analyses of the two lines with the highest levels of transgenic GSK-3beta activity revealed that the phosphorylation status of tau was elevated at the AT8 epitope. These observations strongly suggest that GSK-3beta is an in vivo tau kinase in the brain. Only low levels of expression of GSK-3beta were obtained and it is possible that high levels of GSK-3beta activity are lethal.